Paulo’s Redemption in Paulo Coelho’s Aleph - HARDIAN PURWANDOYO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Abstrak Karya sastra adalah refleksi dari aspek tertentu manusia. Pada diri manusia, seperti jiwa, ada perjalanan menuju penebusan. Penebusan yang terlihat pada novel Aleph karya Paulo Coelho adalah refleksi tentang bagaimana manusia secara alami sering didorong oleh alam bawah sadar mereka sendiri terhadap hal-hal. Seperti dosa dan rasa bersalah. Tesis ini bertujuan untuk mengungkapkan gambaran pengalaman karakter menuju penebusan dan faktor-faktor yang memicunya. Ada dua masalah dalam tesis ini, Novel berudul Aleph karya Paulo Coelho diterbitkan oleh Vintage Books digunakan sebagai sumber data utama. Dalam menjawab rumusan masalah, teori mekanisme pertahanan oleh Sigmund Freud dan teori regresi ke masa lalu digunakan sebagai terapi penyembuhan oleh Brian Weiss. Penggambaran penebusan yang dialami oleh karakter utama ini dianalisis menggunakan konsep penebusan. Perjalanan tokoh utama dalam penebusan digambarkan berurutan sebagai pengalaman penebusan itu sendiri dilakukan. Tesis ini menggambarkan bagaimana karakter utama pengalaman penebusan digambarkan dalam cerita. apakah tokoh utama akhirnya ditebus atau tidak. Penebusan ini adalah yang pertama untuk membuktikan, maka tesis ini akan mengungkapkan faktor-faktor yang memicu dibalik itu. Faktor-faktor apa yang memotivasi dan memicu alam bawah sadar akan terurai dengan menggunakan dua teori yang disebutkan di atas. Kata Kunci: penebusan, mekanisme pertahanan, regresi. Abstract Literary work is the reflection of the human being. In particular aspect, such as psyche, there is a redemption.The journey into redemption seen in Paulo Coelho’s Aleph is the reflection on how human naturally often driven by their own subconscious toward things. Such as sin and guilt. This thesis is aimed to reveal depiction of character’s experience into redemption and what factors that trigger the event. There are two problems of this thesis, Paulo Coelho’s Aleph published by Vintage Books is used as the main data source. In answering the statement of the problems, theory of defense mechanism by Sigmund Freud and theory of regression to past-life used as healing theraphy by Brian Weiss is aplied. The depiction of the characther’s redemption is analyzed using definiton of redemption. The main character’s journey into redemption is portrayed sequential as the experience of redemption itself is done. This thesis portrays how the main character experience redemption is depicted in the story. whether the main character’s is finally redeemed or not. The redemption is the first to prove, then this thesis will reveal factors behind that trigger it. The factors as to what motivate and triggers the subconscious will be unraveled using two theories mentioned above. Keywords: redemption, defense mechanism, regression. INTRODUCTION Literature studies always focused on what is brought by the literary work and analyzed it from many aspects. Many aspects can be taken from a single story but there are not many that is much interesting to study with. Literary studies has been conducted from centuries ago. As Wellek and Warren said we must first make a distinction between literature and literary study. The two are distinct activities: one is creative, an art; the other, if not precisely a science, is a species of knowledge or of learning (3). This is become interesting as Paulo Coelho novels are mostly talk about self-discovery, one thing that can be learn by many. This novel is chosen because it is one of the latest work by the famous writer Paulo Coelho and published in 2010. Aleph is Portuguese-language novel by Brazilian and translated into English by Margaret D. Costa. The author itself is well-known for talking mostly about self-discovery in his novels. Paulo Coelho’s traveling hobby influence many of his work based on his own experience. Including this novel which is said to be his own true story. Fiction though is a work of art in many form that deals with many things that is not factual or unreal which is basically a made up. As far as it goes for a novel it cannot be 100% true story. Therefore, this work is a semi-fiction. Semi fiction is a fictionalized true story or a reconstructed biography. This is interesting as how this novel story goes from the writer’s own experience and the main character is the writer itself. This makes the story more “realistic” though there are addition to the story to make it more suitable for storytelling. For writers, the spices you add to make your plot your own include characters, setting, and dialogue. (Bell, 2004. p. 16). The topic which is brought into discussion later is about redemption that is depicted in the novel. Like the main character in the Alchemist, Paulo is facing a grave crisis of faith. As he seeks a path of spiritual renewal and growth, he decides to begin again: to travel, to experiment, to reconnect with people and the landscapes around him. Redemption itself is an act of seeking forgiveness or to redeem past sin. Sin and redemption are theological categories, not literary themes (Bloom, 2010. P. 16). Yet it is important as mostly people know this terms rather than what Bloom said as Sin is merely error and redemption is only recognition of error. It is true sin is an error in spite which point of view one sees it. If betraying another person is a sin, then it is as well an error that needs to be recognized or redeemed. In this story, the sin-instead using the term error-are the main character, Paulo that found himself in a grave of crisis as a result of his lack of faith. His mentor, J, suggest him to travel again to reconquer his kingdom. In the middle of the journey, Paulo met a mysterious girl later known as his lover in the past life. A girl which he betrayed a lifetime ago. The writer and the main character, Paulo Coelho, is chosen because he is a famous Nobel laureate and his books has inspired many of his readers on self-discovery. Paulo Coelho is a Brazilian lyricist and novelist. He has become one of the most widely read authors in the world today. He is the recipient of numerous prestigious international awards, amongst them the Crystal Award by the World Economic Forum and France's Légion d'honneur. Paolo Coelho was born on August 20, 1946, in Rio de Janeiro, Brazil. He was a rebellious teenager and his parents committed him to an asylum three times. When Coelho was 36 years old, he had a spiritual awakening in Spain and wrote about it in his first book, The Pilgrimage. It was his second book, The Alchemist, which made him famous. He’s sold 35 million copies and now writes about one book every two years. Around 1986, Paulo walked the 500-plus mile Road of Santiago de Compostela in northwestern Spain, a turning point in his life. The walk and the spiritual awakening he experienced en route inspired him to write The Pilgrimage, an autobiographical account of the trek, in his native Portuguese. He quit his other jobs and devoted himself full-time to the craft of writing. After the event of the pilgrimage, Coelho found himself once more on a state of lacking faith, thus set a journey like he previously did. This journey through Trans-Siberian railway later written in this novel Aleph. Coelho has said in interviews that Aleph is one of his most personal novels to date. The story finds Paulo, which is how Coelho refers to himself in writing, struggling with a serious crisis of faith. When Paulo complains to his master, the cryptically named J., about his dissatisfaction with life and the stagnation of his spiritual growth, J. advises him to get back on track by seizing the present moment, a mystic space called the Aleph. Aleph is the first letter of the Hebrew alphabet. Like Coelho’s previous books, Aleph also teaches about self-development. Those who are used to reading Coelho will enjoy Aleph as much as “The Zahir,” which means “the obvious” or “conspicuous” in Arabic and was banned in Iran, or “The Witch of Portobello,” which explores religious themes. Aleph is an engaging book, especially for people facing complicated problems in their lives. For some, the book may help in the discovery of inner peace, the realization that life is a beautiful journey that’s filled with wonder. The concept of reincarnation might be a bit of a stretch for some readers, but one dos not have to believe it to enjoy the book. Reincarnation is a process of coming back to life in another body. In the novel, he claimed to have reincarnated many times and the further he could remembered his past live nearly 400 years ago. Starting in Africa and then crossing Europe and Asia via the Trans-Siberian Railway, he undertakes a journey to revitalize his energy and passion. Even so, he never expects to meet Hilal. A gifted young violinist, she is the woman Paulo loved five hundred years before - and the woman he betrayed in an act of cowardice so far-reaching that it prevents him from finding real happiness in this life. Together they will initiate a path that teaches love, forgiveness and the courage to overcome life's inevitable challenges. The novel depicts the journey of the author, Paulo Coelho and a woman named Hilal and several colleagues of the main character or the author himself. The novel starts with Paulo talking to his Master about the dissatisfaction in Paulo’s life and the stagnation of his spiritual growth. As per the suggestion from his Master, Paulo sets off onto a journey starting from Africa, and then to Europe and Asia via the Trans-Siberian Railway. Most of the novel or rather the book describes about the author’s experiences during the train journey he took with his publishers and a girl whom he meets in the journey. The journey itself is a way to renew Paulo’s spiritual as suggested by J. Several times later he met with a girl named Hilal which accompany him along the journey. At some moment in the train, in the middle of their conversation, Paulo experiencing something that was happened before his present life. He gain a memory of himself several hundred before while looking at Hilal’s eye. They were in aleph. Paulo remembered his past live as he consider himself sinful for he did prevent the event of 8 women who were hung to death for their sin. This encounter make a secondary objective that make the entire journey. Paulo now seeks redemption from Hilal as he thinks that he is the fifth of eight women to meet in his lifetime. Those women are victims of Paulo previous life that are sentenced to death for committing sins. He feels guilty for he couldn’t do anything to save them. This feels of guilty keep haunting him along the journey. In order to get rid of this feeling, Paulo needs Hilal to redeem or to forgive his past sin. This inspire the discussion on why the redemption occurred and how this problem theoretically explained METODE When facing a literary work the main thing to be concerned is the content which consists of characters, characteristics and story. Besides that, also concern the purpose and the message intended by the author. This thesis uses descriptive qualitative design (the data will be described or explained by words without numbers) to describe Paulo’s redemption and the factors that trigger it. This study uses a paperback novel entitled Aleph by a famous writer/novelist Paulo Coelho that has been translated into English by Margaret D. Costa and published by Vintage Books a division of Random House in 2011 as the source data. The study will use the quotation taken from the novel to indicate the existence of the process of redemption and the factors beneath it. Collecting data for this study is through reading method. This method is applied by reading text several times that is included as the object study. After that it will be classified for further discussion. Data will be processed by reading repeatedly, then choose several part from the novel that indicate the topic discussed and relate it with a particular theory. Thus it locate the factor and depict the process of redemption. This study applies the descriptive qualitative method in analyzing data, means that the data will be described and explained by words without numbers. Thus it will be analyzed with the theory related. The definition of redemption applied to explain how is the redemption depicted in the story. Then the psychoanalysis theory applied to detect the subconscious aspect of Paulo and past-life regression as healing therapy theory that becomes the spiritual remedy that Paulo thinks he needs it to renew himself. Further explanation of the theory will be discussed in the second chapter. DEPICTION OF REDEMPTION The goal/redemption is the condition where Paulo is supposed to be spiritually renewed and forgiven. His spirit is once again restored in full capacity. His old wound has healed and his feeling of guilty has gone. The redemption point is in the renewal point of his spiritual state and forgiveness of Hilal and the finish line of his journey into his own kingdom. Redemption is the main part of this study. Redemption itself defined as receiving forgiveness for the commision of sin. Sin and redemption are theological categories, not literary themes (Bloom, 2010. P.16). Redemption is a religious concept referring to an effor of seeking forgiveness from past sins and errors. Bloom suggest that error, not sin, is an authentic literary concept, and that recognition, rather than redemption, is the inevitable literary theme that emanates from error (16). Sin is defined as error while redemption is the recognition of the error. The main character in this novel commited a certain sin that later he recognite and made him to seek for forgiveness. Paulo is finally renew himself by acting as a street beggar. Before the journey, he told J. that he feels corrupted by routines thus need to renew himself. J. once said to Paulo that it’s what you do in the present that will redeem the past and thereby change the future (10). This implies that what his current actions that leads to a better or even worse future and now it is up to him to decide. J. also states to Paulo that he is not here anymore, you’ve got to leave in order to return in the present, go and reconquer your kingdom (2011, p.11). J. as his mentor convinced Paulo to embark to a journey and seek for redemption Paulo. He replied that “If I need to travel in time, why do I have to travel in space as well ?” J replies, “Because we all have the possibility of redemption, but for that to happen, we have to seek out the people we harmed and ask their forgiveness” (2011, p.13). This motivates him to go seek for redemption and the possibility that it is exist is there. As J. suggested he must embark on a journey as he always done. Paulo famous known as a traveler novelist. His books mostly talks about self-development or philosophy lesson he gathered from his experience during his journey. So J. suggested this by the fact that Paulo loves to travel and recently has corrupted by his own routines. He needs to be refreshed, to be once again renewed so that he could become himself again. Paulo receive his forgiveness from Hilal for his past sin. Paulo took her in Aleph to travel her into the past to connect her with her past-life person. The girl apparently expressing her forgiveness towards Paulo. Hilal is redeeming not only Paulo but everyone. She forgives everyone that have done evil upon her. Paulo has reached his goal, evidence that he has been redeemed. When Paulo took her in Aleph, Hilal was in a relaxed state. This state helps Paulo to extract the information and use it to his purpose. Dr. Weiss once stated that this is the second pattern while accessing and describing the pastlife memories. It is called the key moment flow. In key moment flow, the subconscious knits together the most important or relevant moments from a cluster of lifetimes, the key moments that will best elucidate the hiddden trauma and most quickly and powerfully heal the patient (Weiss, 1992: 34). In the end Paulo is redeemed and acquire his own kingdom back. This can be done in thoughts but that would’nt serve him, to experience physically is way more important than only think about it. FACTORS OF REDEMPTION the second statement of the problem which is to reveal the factors that triggers Paulo to experience redemption will be revealed. Based on the process, the assumed factors that triggers redemption are sin and guilt. Sin committed by Paulo will be depicted and the guilt also depicted in separate parts. Within those parts, the theories which are defense mechanism and past life regression healing therapy will be applied. Defense mechanisms are the various techniques the ego employs to control instincts and ward off anxieties. All of us make use of these mechanisms from time to time, although we are seldom conscious of doing so. Paulo does the same thing, he only aware of his own sin and guilt but the mechanisms progresses in his subconscious. The second theory is the Past-life regression healing therapy. In the story, Paulo practices a certain method to bring him into a state named aleph. In the aleph, he is able to reveal everything in the universe at once. Including his previous lives. Thus the similarity of his practice lies on the state he is being at. The past-life regression healing therapy uses this to reveal the past life and healing it in the process by many ways necessary. SIN Sin is the substance of all Paulo’ activity in this novel. Though it is not his present time sin, it still haunt him enough to embark on a journey. In analyzing sin,theory of past-life regression healing therapy advised by Dr. Brian Weiss is used. Regression therapy is the mental act of going back to an earlier time, whenever the time may be, in order to retrieve memories that may still be negatively influencing a patient’s present life and that are probably the source of the patient’s symptoms (Weiss, 1992. p.27). The therapy applied the hypnosis method to put the patient into a state that s required for the regression therapy. Hypnosis is the main technique used to help patients to access their past memories. It is a state of focused concentration, of the sort many of us experience every day. (Weiss, 1992. p.24). In the novel, Paulo applies some sort of method to put both himself and Hilal into a hypnotized state, thus called Aleph. This leads into a suggestion that Aleph itself is a state when mind is open wide to invite the subconscious out. The hypnosis applied by Paulo then used to put Hilal into her past-life to reminisce a particular event in the past. Hypnosis puts the patient in a state that holds great potential for healing by giving the patient access to subconscious mind (Weiss, 1992. p.24). ). By doing this, Paulo believe that it could heal his old wound and achieve redemption. The Aleph used in the story suggests that it is similar with the method Dr. Weiss practice. The patient is put into a relaxed state then extract the information needed from the present lifetime or the previous lifes. Dr Weiss found that hypnosis combined with regression therapy plumbs the uncosnscious more deeply than do psychoanalytic techniques like free association, in which the patient remains in a relaxed but conscious state while merely closing the eyes (Weiss, 1992: 30). He mentioned to his mentor, J, that traveling to past lives is actually possible. Though it is full of risks to take, but it is considered worth to try to heal his old wounds. Past-Life regression mentioned there held some risks to bear. It will destroy his present time and continually giving negative effects toward him. It seems from the quotation above that Paulo have done the regression at least more than once. It indicates of what Weiss said in his book that in a successful therapy to uncover early trauma, the patient will suffers a frequent relapses (Weiss, p.29). Aware of such risky decision, Paulo seems insists on traveling into the past again to uncover his old wound. Weiss said that based on his experience while treating Catherine, one of his patient that regression to anearlier period of this present-day life-time is usally fruitful enugh for the most of the remainder. (Weiss, p.28). This urge to repeat or repetition compulsion was the name given by Freud to describe the often irresistible urge to redramatize or reenact emotinal, typically painful, experiences that occured in one’s past (Weiss, p.27). This urge seems perceptible in Paulo’s words to his mentor above. He insists to travel into the past though his mentor clearly refuse to take his idea because there are possible negative effects. The effect though is proven to be redramatized by Paulo and he reenact the emotional feeling with metaphorical word like a fire that could burst and destroy anything within its path GUILT Guilt is an emotional experiences that occurs when a person realizes or believe that she/he has violated his own moral standard (Cengage, 2005). In analyzing guilt, theory of defense mechanism is applied. Psychoanalysis is a psychological and psychotherapeutic theory conceived in the late 19th and early 20th centuries by Austrian neurologist Sigmund Freud. Here the psychology theory were applied to a work of literature. By